Constructing public relations as a women’s profession in Russia - Tsetsura, Katerina (Instituto de Investigación en Relaciones Públicas, 2014)
This study examines how public relations can be understood, perceived, and ultimately constructed as a profession through professionals’ everyday discourses. The article explores what it means for public relations practitioners to be considered professionals in the field that is actively developing in many parts of the world. The goal was to expand the understanding of what constitutes the profession of public relations through a qualitative analysis of workcentered discourses of practitioners. The results demonstrated that, specifically in Russia, similar to many other countries, public relations is often seen as a profession that is better suited for women than men due to historical, socio-economic, and societal factors as well as due to pre-conceived notions about public relations. This study contributes to a new theoretical understanding of public relations as a socially constructed profession and demonstrates how construction of this profession can both propel and slow down the development of the practice
Construyendo las relaciones públicas como una profesión de mujeres en Rusia
Keywords: Relaciones públicas; Mujeres - Trabajo; Public Relations; Women; Profession